Seismic Evaluation Of Low To Meduim Rise Of Regular Rc Building - Aidy, Siti Hajar Noor (Universiti Sains Malaysia, 2017)
Earthquake is caused by the sudden release of energy or an unexpected movement from the earth surface. Tsunami that occurred on the 24th December 2004 caused by earthquake with a magnitude of 9.1 had brought damages not only to structural buildings but also to human lives. Research on seismic performance had been carried out over the past decades to evaluate the risk and seismic vulnerability under earthquake. The main objective for this study is to determine the performance of regular 3D moment resisting concrete frame (MRCF) under seismic provision. Nonlinear static and dynamic analysis had been used in this study to evaluate the performance of low to medium rise RC building. These analysis provide information in evaluating the performance of the structural building under earthquake. This study implemented 3D structure to represent real building under seismic loading. Three different storey, N: 3, 6, and 9 were used as the structural models which some of the parameters used were adopted from Hatzigeorgiou and Liolios (2010). Seven single ground motions data were employed to represent the seismic ground motion. STERA 3D and SAP 2000 software were used to run the analysis. Results from the pushover analysis shows that nine storey has the highest percentage of drift compared to three and six storey. The drift shear relation curve exhibited that higher storey levels has the highest displacement. The Incremental Dynamic Analysis (IDA) shows that the displacement of the building increases when there is an increase in PGA. It can be proved that each earthquake ground motion has a different value of displacement for the structure.